Power Factor Improvement Using Capacitor Controlled Based on Dimmers - Prasetia, Abdul Muis; Sartika, Linda; Syamri, Mohammad (DPTE FT UNY, 2025)
The utilization of electric power predominantly involves inductive loads, which result in lagging voltage waves that increase power consumption beyond what is effectively utilized, thereby reducing power factors and causing energy losses. To mitigate reactive power from inductive loads, capacitors are commonly installed in parallel. However, conventional fixed capacitor banks often lead to suboptimal results due to improper sizing. This study presents an innovative power factor correction device utilizing dimmer-controlled capacitors for dynamic capacitance adjustment. The research offers a cost-effective alternative to microcontroller-based systems while providing real-time adaptability for varying loads. The system enables precise control of capacitance without complex programming. The experimental approach uses six parallel-connected capacitors (2.5μF each), controlled by a dimmer circuit with TRIAC, DIAC, and potentiometer components. Testing is conducted with variable inductive loads ranging from 1.7 H to 6.8 H, simulating laboratory conditions with potential for scaling to real-world applications. The methodology includes baseline measurements, capacitor compensation, load variation analysis, and performance evaluation. Results demonstrate power factor improvement from 0.55 to 0.85 using a capacitance range of 0.6299μF to 15μF. The dimmer-controlled approach effectively increases active power while reducing reactive power from 56.198 VAR to 33.773 VAR, significantly improving voltage stability under varying load conditions.